An experimental and theoretical study of the valence shell photoelectron spectra of 2-chloropyridine and 3-chloropyridine - Holland, D.M.P.; Powis, Ivan; Trofimov, A.B.; Menzies, R.C.; Potts, A.W.; Karlsson, L.; Badsyuk, I.L.; Moskovskaya, T.E.; Gromov, E.V.; Schirmer, J. (AIP Publishing, 2017)
The valence shell photoelectron spectra of 2-chloropyridine and 3-chloropyridine have been studied both experimentally and theoretically. Synchrotron radiation has been employed to record angle resolved photoelectron spectra in the photon energy range 20–100 eV, and these have enabled anisotropy parameters and branching ratios to be derived. The experimental results have been compared with theoretical predictions obtained using the continuum multiple scattering Xα approach. This comparison shows that the anisotropy parameter associated with the nominally chlorine lone-pair orbital lying in the molecular plane is strongly affected by the atomic Cooper minimum. In contrast, the photoionization dynamics of the second lone-pair orbital, orientated perpendicular to the molecular plane, seem relatively unaffected by this atomic phenomenon. The outer valence ionization has been studied theoretically using the third-order algebraic-diagrammatic construction (ADC(3)) approximation scheme for the one-particle Green’s function, the outer valence Green’s function method, and the equation-of-motion (EOM) coupled cluster (CC) theory at the level of the EOM-IP-CCSD and EOM-EE-CC3 models. The convergence of the results to the complete basis set limit has been investigated. The ADC(3) method has been employed to compute the complete valence shell ionization spectra of 2-chloropyridine and 3-chloropyridine. The relaxation mechanism for ionization of the nitrogen σ-type lone-pair orbital (σN LP) has been found to be different to that for the corresponding chlorine lone-pair (σCl LP). For the σN LP orbital, π-π* excitations play the main role in the screening of the lone-pair hole. In contrast, excitations localized at the chlorine site involving the chlorine πCl LP lone-pair and the Cl 4p Rydberg orbital are the most important for the σCl LP orbital. The calculated photoelectron spectra have allowed assignments to be proposed for most of the structure observed in the experimental spectra. The theoretical work also highlights the formation of satellite states, due to the breakdown of the single particle model of ionization, in the inner valence region.